Optimalisasi Wakaf Uang di Pasifamal.id dalam Mewujudkan SDGs Program Dana Abadi Modal Kerja Halal UMK Kota Yogyakarta - M, W Cinta; Hilmiawan, Gigih Aulia; Ayu, Navirta (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The use of digital technology in Indonesia to attain the Sustainable Development Goals (SDGs) remains suboptimal. This research examines the platform pasifamal.id, which integrates social accounting to improve transparency and augment public engagement in the halal working capital endowment initiative for Micro and Small Enterprises (MSEs) in Yogyakarta. This study aims to evaluate the efficacy of optimizing cash waqf using the platform in promoting sustainable development. We gather data through qualitative case studies, observations, and comprehensive interviews nazir and stakeholders, supplemented by pertinent documents. Data analysis is performed utilizing open coding, axial coding, and selective coding phases, following the Corbin and Strauss technique, to provide a thorough knowledge of cash waqf management and its impact on the SDGs. Key findings highlight three aspects: first, the optimization of cash waqf at pasifamal.id in realizing the SDGs of the halal working capital endowment fund program for MSEs in Yogyakarta City; second, strategy for raising cash waqf funds at pasifamal.id; and third, community participation and factors driving cash waqf at pasifamal.id. This platform provides interest-free funding for MSEs, and the use of social accounting facilitates the accurate assessment of social impactthe importance of strengthening brand image and improving product quality to attract consumers to hybrid vehicles.
Keywords: Cash Waqf; Halal Working Capital; Pasifamal.Id; Sdgs; Social Accounting